Moving target shooter`s attention control analysis - Kadutskaya, L. A.; Posokhov, A. V.; Mironova, T. A.; Domracheva, E. Yu. (Theory and Practice of Physical Culture, 2019)
Shooting a moving target may be described as the standard sequence of psychomotor actions. The beginner shooter training systems give a special priority to the attention control skills to effectively respond to and control the sport-specific sensations and data flows. Our study has found that the modern moving target shooting sport is increasingly demanding to the shooter`s mental control qualities including the attention control ones. The attention controls shall be perfect to timely focus the body and mind and fast switching attention skills when necessary for success in the shooting competitions. We obtained and analyzed the attention control test rates including the attention focusing, accuracy, success and attention switching rates versus the shooters` skills levels (Candidate/ World Class/ Honored Masters of Sport). It was found that the attention control qualities and skills are largely predetermined by the individual genetic type and, hence, it may be difficult in modifying to develop an optimal balance of the attention focusing and switching qualities. On the whole the study tested the World Class/ Honorary Masters of Sport with the highest attention focusing and switching rates in shooting a moving target. This finding may be interpreted as indicative of the long-term training process making it possible to improve to a degree the attention control skills.